Mode of inheritance of common bean (Phaseolus vulgaris L.) traits for tolerance to low soil phosphorus (P) - Kimani, JM; Kimani, P.M.; Githiri, SM; Kimenju, J.W. (Springer, 2007)
Low soil phosphorus (P) has been singled out as a major constraint leading to perpetually low bean (Phaseolus vulgaris L.) grain yield far below the expected yield potential. In developing countries beans are mainly produced by small-scale farmers who have little capacity to use inorganic fertilizers to replenish their soils. Yet bean production contributes significantly to their income and provides a cheap source of protein to rural and urban populations. The genetics of inheritance of the traits conferring low soil P tolerance is not well understood. The identification and understanding of the mode of inheritance of the traits for P-efficiency in bean will go along way in boosting bean yields through development of varieties adapted to low soil P. The objective of this study was to determine the inheritance of the traits conferring adaptation to low soil P, for the important large seeded red mottled bean market class. Three parents with known tolerance to low soil P were crossed with five adapted but non-tolerant genotypes in an 8 × 8 half diallel mating scheme. The resulting F1 seeds were evaluated under medium and low soil P conditions at two locations. Both general combining ability (GCA) and specific combining ability (SCA) variances were highly significant (P ? 0.01) for all five characters studied except SCA variance for root dry weight at one location. The magnitude of GCA variance was up to twelve times higher than the SCA variance. The GCA:SCA ratio varied from 0.62 to 0.96 for the characters studied. The additive genetic variance was more important than the dominance variance for tolerance to low soil P.